A lover's cock and other gay poems gay sunshine press, san francisco, 1980. - Antonia Dilamar Araújo (Ilha do Desterro)
The union of the two French symbolist poets Arthur Rimbaud and Paul Verlaine revolutionizes the nineteenth and the twentieth centuries with its homoerotic poems. But only now they are having their works printed by Gay Sunshine Press. The collection of erotic poems - A Lover's Cock - reveals to the reader the sexual liberation which happened a century ahead of its time. Rimbaud and Verlaine's is a bold, strong and direct style for a period when to be gay was infamous and unacceptable. In fact, they were ostracized by the Parisian society because of their rude behaviour.